1966
DOI: 10.1042/bj0980782
|View full text |Cite
|
Sign up to set email alerts
|

The isolation and partial characterization of glycolipids of normal human leucocytes

Abstract: 1. The lipids of purified human leucocytes were extracted with chloroform-methanol and the extract was washed with water. Glycolipids, isolated by Florisil chromatography, were subjected to mild alkaline hydrolysis and the alkali-resistant fraction was fractionated on a silicic acid column. 2. Three classes of glycolipid were separated. The less polar, containing 3.6% of the total glycolipid hexose as galactose, was tentatively identified as ceramide monohexoside. The major glycolipid fraction was characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1969
1969
1982
1982

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…The presence of a high proportion of 2-hydroxy fatty acids indicated a major difference from the fatty acid compositions of human leucocytes glycosphingolipids (1). The fatty acid compositions of the total glycosphingolipids of blood lymphocytes, thymus and lymph nodes, and thymus ceramides from one small male pig are shown in Table III.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The presence of a high proportion of 2-hydroxy fatty acids indicated a major difference from the fatty acid compositions of human leucocytes glycosphingolipids (1). The fatty acid compositions of the total glycosphingolipids of blood lymphocytes, thymus and lymph nodes, and thymus ceramides from one small male pig are shown in Table III.…”
Section: Resultsmentioning
confidence: 97%
“…Even so, there are wide variations in the amounts of these minor components in different tissues, and, compared with most tissues, the white blood cells are relatively rich in glycosphingolipids. The white cells, which have been examined in a limited number of species (1)(2)(3), contained predomi- nantly either dihexosyl or trihexosyl ceramides (GL-2, GL-3). It has been shown that glycolipid biosynthesis occurs in bone marrow cells (2), as well as in normal human leucocytes (4,5), and that in immature leucemic cells it occurs at an accelerated rate (5).…”
Section: Introductionmentioning
confidence: 99%
“…The acidic fractions of heart GSL were carefully examined for the presence of su!fatides, and it was concluded either that they are not present or that they constitute a very minor component. This is not surprising since sulfatides have not been detected in a variety of extraneural human tissues including skeletal muscle (2,13,(20)(21)(22). They are major components of the human kidney (24) and the thyroid (7).…”
Section: Discussionmentioning
confidence: 99%
“…The results of GSL were expressed in nmoles cal-Culated from the area of the glucose peaks (6,7). Sphingosine was determined (12) as described previously (13). The sialic acid content of the gangliosides was determined by the modified (14) method of Svennerholm (15).…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…The acidic lipid fraction was dried by evaporation of solvents under reduced pressure, followed by lyophilization, and the dry residue was submitted to mild alkaline treatment [ 5 ] , followed by Folch partition [26].…”
Section: Isolation and Purificationmentioning
confidence: 99%